2019
DOI: 10.1016/j.neuroscience.2019.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Melanopsin-Containing ipRGCs Are Resistant to Excitotoxic Injury and Maintain Functional Non-Image Forming Behaviors After Insult in a Diurnal Rodent Model

Abstract: Intrinsically photosensitive retinal ganglion cells (ipRGCs) are critical for the light signaling properties of non-image forming vision. Melanopsin-expressing ipRGCs project to retinorecipient brain regions involved in modulating circadian rhythms. Melanopsin has been shown to play an important role in the way animals respond to light, including photoentrainment, masking (i.e., acute behavioral responses to light), and the pupillary light reflex (PLR). Importantly, ipRGCs have been shown to be resistant to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Melanopsin is a photopigment located in intrinsically photosensitive retinal ganglion cells (ipRGCs) ( Beaulé et al, 2003 ) which project to retinorecipient brain areas to modulate non-image forming vision ( Hattar et al, 2006 ) including entrainment of the master clock to the light-dark cycle, the pupillary light reflex (PLR), and masking to light in nocturnal mice ( Hatori et al, 2008 ). In diurnal Nile grass rats, it has been recently shown that these melanopsin-containing ipRGCs are resistant to excitotoxic injury and are capable of maintaining functional non-image forming behaviors ( Fogo et al, 2019 ). One of the retinorecipient brain areas that receives direct input from these ipRGCs is the SCN, the master clock in mammals; brain areas downstream of the SCN also receive direct input from light ( Berson et al, 2002 ; Warren et al, 2003 ; Dacey et al, 2005 ).…”
Section: Exogenous Stimuli That Affect Masking Behaviormentioning
confidence: 99%
“…Melanopsin is a photopigment located in intrinsically photosensitive retinal ganglion cells (ipRGCs) ( Beaulé et al, 2003 ) which project to retinorecipient brain areas to modulate non-image forming vision ( Hattar et al, 2006 ) including entrainment of the master clock to the light-dark cycle, the pupillary light reflex (PLR), and masking to light in nocturnal mice ( Hatori et al, 2008 ). In diurnal Nile grass rats, it has been recently shown that these melanopsin-containing ipRGCs are resistant to excitotoxic injury and are capable of maintaining functional non-image forming behaviors ( Fogo et al, 2019 ). One of the retinorecipient brain areas that receives direct input from these ipRGCs is the SCN, the master clock in mammals; brain areas downstream of the SCN also receive direct input from light ( Berson et al, 2002 ; Warren et al, 2003 ; Dacey et al, 2005 ).…”
Section: Exogenous Stimuli That Affect Masking Behaviormentioning
confidence: 99%
“…The RGCs that make up the papillomacular bundle may be particularly vulnerable due to their more limited blood supply (14), increased exposure to oxidative stress generated by passage of light (43), and the relatively smaller caliber of the parvocellular RGC axons, which may physically restrict the transport and maintenance of mitochondria (44). Intrinsically photosensitive RGCs (ipRGCs) appear to be resistant to degeneration in this disease and in many animal models of neuronal damage (45)(46)(47). This is consistent with the finding that patients with DOA appear to have preserved physiological diurnal rhythms and pupillary light reflexes (45) because ipRGCs are crucial for circadian entrainment and nonvisual light perception (48)(49)(50).…”
Section: Pathogenesismentioning
confidence: 99%
“…The projection of ipRGCs-SCN in the Nile rat ( Arvicanthis niloticus ) is comparable to that of the Syrian hamsters 119 . However, there are differences in sensitivity to phase movement between the two species on the NMDA-induced PRC 120 , 121 , which is also reflected in the strong resistance of Arvicanthis niloticus to NMDA 122 .…”
Section: Photosensitive Regulation Of Circadian Rhythms By Opn4mentioning
confidence: 99%
“…The projection of ipRGCs-SCN in the Nile rat (Arvicanthis niloticus) is comparable to that of the Syrian hamsters 119 . However, there are differences in sensitivity to phase movement between the two species on the NMDA-induced PRC 120,121 , which is also reflected in the strong resistance of Arvicanthis niloticus to NMDA 122 . ipRGCs also express a peptide neurotransmitter called pituitary adenylate cyclase-activating peptide (PACAP) and colocalize with glutamate at the terminals of RHT in the SCN 123,124 .…”
Section: Contribution Of Opn4 To Mammalian Circadian Rhythmsmentioning
confidence: 99%